Sacred Spaces in Transition: A Glimpse into the Situation of the Evangelical (Lutheran) Church A.C. in Romania - König, Heidrun (Review of ecumenical studies, 2021)
For sacred spaces, motion/movement means not only the takeover by other denominations, but also denominational changes, such as the Reformation. The article highlights, with varying intensity, the major movements of sacred spaces in the more than 800-year history of the present-day Evangelical Church A.C. in Romania: the Reformation, the Habsburg rule, the consequences of World War II in Northern Transylvania, and the present - with selective recourse to the tools of Memory Studies (Erinnerungsforschung), in order to trace the paradigm shift caused by the Reformation in relation to sacred space, or to evaluate the mass handover/ transfer of church buildings in Northern Transylvania in the horizon of this analysis, and concluding with a brief art-historical and even homiletic consideration.